Kogegruber i New Guineas højland - Lerche, Grith (Kuml, 1969)
A Cooking Pit in New Guinea Travelling in the Far East in 1968, I visited the Australian part of the New Guinea highlands, and had in a village called Alipe Manya near the town Mount Hagen the opportunity to observe how the natives used hot stones to cook their food. Archaeologists have difficulty in interpreting the many sorts of pits they find, often in curious places, and the purpose of this description of the preparation and use of a certain type of cooking pit in New Guinea is first and foremost to give an idea of how some of the excavated pits may have been used. Different interpretations have been given of pits excavated in settlements in Denmark since the last century [1]. Three main types of pits are now recognized from the Stone, Bronze and Iron Ages, but only pits with charcoal at the bottom, covered by a layer of burnt stones, are treated here, because analogous pits are still in use in New Guinea. The staple food and main crop in the Mt. Hagen area of New Guinea is sweet potatoes (Ipomea batatas), called "kau-kau" by the natives in Alipe Manya. These are grown in fields divided into beds by deep drainage canals, and it is the women's task to procure the daily amount of sweet potatoes with their digging sticks. The preparation of a cooking pit started one afternoon about 4 o'clock outside one of the grass huts. Some sods were lifted and a hole dug, 50 cm. in diameter and not more than 20 cm. deep. The necessary material was collected: about 40 vulcanic stones of fist size, dry firewood and leaves. Firewood was chopped with a steel axe (fig. 1). Usually an ember was taken from the fireplace, but in this case fire was obtained by friction. Tinder consisting of dry flowers and pit-pit grass was placed under a split branch holding a wedge, and a string of wild bamboo slung round the branch moved rapidly up and down. This quickly ignited the tinder (fig. 2-3). In the pit, dry grass and chopped wood were ignited with a tuft of burning grass. A frame about 70 cm. in diameter was made of longer pieces of firewood. On this platform, about 7 cm above ground level, all the stones were piled in a layer 15 cm thick (fig. 4-5). On top of this "stone fire", some twigs of the casuarina tree were placed to add flavour, in this way a sort of indirect spice. After the fire had burnt down and the heated stones had fallen into the pit, most of them were removed with a forked branch and kept hot on a small fire nearby, while the rest of the stones and charcoal lined the pit about 7 cm. below ground level (fig. 6-7). The cooking pit was now ready. At the bottom were placed a bunch of cordyline leaves-also called arse leaves because they are used for the back of the men's dress-and 5-6 leaves of the wild fig. In both cases the coarsest part of the sheaths had been cut off. Above these were placed a layer of hot stones and then the food consisting of cabbage, tiny green leaves, pit-pit shoots, sweet potatoes, Irish potatoes and taros, all peeled for our benefit. On top and in between the food more stones were laid. The underlying cordyline and wild fig leaves were folded up around the food and the cooking pit then sealed with more leaves, stones and turves. The preparation and filling of the pit took hardly more than an hour. Well covered, the food cooked for nearly one hour, and then the turves, pit-pit grass, leaves and hot stones were removed. Salt was added and the well cooked food was very tasty (fig. 8-10). There was enough to satisfy half a dozen people. A pit with burnt stones and charcoal would be the only thing left after this cooking, while all organic remains of plants and of the meal would have disappeared unless they had been charred (fig. 12). Besides open-air cooking pits, people in Alipe Manya and the locality of Mt. Hagen had indoor cooking pits. One of these was 60 X 70 cm. in size (fig. 13). Nowadays an empty oil barrel is often used instead of a wooden vessel. People in the highlands neither made nor used pottery. The preparation of food -vegetable as well as animal- by means of hot stones in cooking pits, is well known from different parts of the world [2]. Pits are known from many Iron Age settlements. Some have also been interpreted as cooking pits. They are difficult to date if not found in connection with a settlement, although a radiocarbon dating of the charcoal is of course possible (fig. 14). At the Roman Iron Age settlements Sorte Muld and Dalshøj in Bornholm many pits have been excavated. Those with burnt stones and charcoal are cooking pits [3]. At Swedish Iron Age settlements at Vallhagar on Gotland and on Øland there were many indoor cooking pits, besides the fireplaces [4]. Recently a large number of cooking pits, 44, from about the beginning of our era, were excavated at Nissehøj, Zealand. Some had been used more than once. The subsoil was often burnt red, and they contained much soil mixed with charcoal and burnt stones (fig. 15). Also at the Viking settlement Lindholm Høje, cooking pits were found among the houses (fig. 16), as well as at the medieval village excavation Store Valby, Zealand. The literature, especially the Icelandic sagas, often mentions cooked meat as a dish of our ancestors (Rigsthula, Olav Tryggvesson's saga, Grágas) [5]. From some passages in Haustlong and Hymer's poem, as well as in Skáldskarparmál, we learn that meat was cooked in well covered cooking pits called seyðir [6]. The evidence from linguistic research and the literature about cooking in pits is supplemented by the excavations in Iceland [7]. Another method very similar to the above-mentioned has been employed since the Stone Age and has been traditional up to our times, especially in connection with brewing, where a large amount of hot water is required. Hot stones are dropped into a container full of water and the water then used for boiling meat, etc. Remains from this sort of cooking consist of mounds of broken and burnt stones, because the rapid cooling of hot stones makes them burst [8]. Some open-air cooking places of this type from the Bronze Age have been excavated in Ireland and the excavators have made very successful imitative cooking experiments [9]. Hot stones are common to the two methods and one can do without fragile pottery or expensive metal vessels in both cases. Furthermore, the problem of finding vessels large enough does not arise. From the circumstances of discovery it should be possible to distinguish the one cooking method from the other by the presence or absence of charred wood, the depth of the pit, the amount of burnt and burst stones, etc. The archaeological evidence for cooking pits is found especially in a context where the community had a large livestock, or among hunters. It would be of interest if the charred remains from the pits were to be subjected to scientific examination. It should be possible to find plant remains as well as fragments of bone which would give further information on what had been prepared in the pits. Grith Lerche